Incidence of unilateral consumption taxes on world carbon emissions - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2011)
This note investigates the suitability of unilateral consumption taxes for alleviating climate change in a two-period two-country general equilibrium model with a finite stock of fossil fuel. We analyze the incidence of a unilateral consumption tax in the first period on world carbon emissions. If countries are identical or if the taxing country imports both fossil fuel and consumption goods in the second period, increases in the tax rate lower first-period carbon emissions in both countries implying a negative rate of carbon leakage.
Keywords: H22; Q38; Q58; 330; unilateral consumption tax; world emissions; leakage; Verbrauchsteuer; Steuerwirkung; Kohlendioxid; Luftverunreinigung; Klimaschutz; Zwei-Länder-Modell; Allgemeines Gleichgewicht; Theorie